Perancangan dan Pengujian Pemanas Air Tenaga Surya yang disertai Material Berubah Fasa (PCM) sebagai Medium Penyimpan Panas - M. Syahril Gultom (Jurnal Dinamis, 2013)
AbstractSolar energy is the most abundant renewable energy source that is available in everywhere.On of the most promising application of solar energy resource is solar water heater. There aremany needs for hot water, they are home appliance, hotel, industry, hospital, etc. Solar energy isavailable in daytime, on the other hand, utilizing hot water is usually afternoon and evening. Thus,thermal storage with phase change material is promoted here. This work is a study on solarwater heater with phase change material (PCM) as a thermal storage. Research anddevelopment on a solar water heater with phase change material as a thermal storage need longprocess. It consists of, usually, design, fabricating, testing, optimizing, and pilot scaledevelopment. Here, design, fabricating and testing the solar water heater with PCM as thermalstorage are carried out. The main dimensions of designed solar water heater are: length of 2m,wide of 1 m, and thickness of 0.25m. The PCM is made of Stearic acid and it is loaded with 75 kg.The solar water heater is tested by exposing to solar radiation. The results shows that themaximum temperature of the absorber can be up to 107oC and the incident energy is 33.27 MJ,energy loss of 8.36 MJ and storage energy of 12.6 MJ. Thus efficiency of the solar water heateris 37.87%. The main conclusion here is that a simple solar water heater with PCM can befabricated with a good thermal efficiency.Keywords: Solar Energy, Water Heater, Phase Change Material